Pengetahuan dan frekuensi konsumsi fast food pada kelompok usia dewasa muda di Kepulauan Riau - Anggraini, Citra Dewi; Herviana, Herviana; Rizma, Amalina (Program Studi Gizi, 2024)
Fast food is defined as food with low nutritional quality, namely high in sugar, salt, fat and low in fiber and served with a fast process. The choice of food consumption in individuals is influenced by several factors, one of which is the knowledge possessed by the individual. The purpose of this study was to analyze the relationship between nutritional knowledge and the frequency of fast food consumption habits. The research design used an observational type with a cross-sectional design. The number of samples in this study was 158 people with a total sampling technique. The results of the study showed that subjects who had good knowledge were 95 people (60.2%) and less knowledge were 63 people (39.8%). Individuals who had a frequent frequency of fast food consumption were 82 people (51.9%) and rarely were 76 people (48.1%). There was no relationship between nutritional knowledge and the frequency of fast food consumption in the young adult age group in the Riau Islands.